THE EFFECTIVENESS OF TAI CHI IN REDUCING DEPRESSION LEVELS IN THE ELDERY - Rahmah, Tasya Aulifiah; Yuniartika, Wachidah (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Older adults are a group that is vulnerable to psychological changes, including depression. Depression in older adults can lead to a decline in overall well-being and increase the risk of additional health complications. One non-pharmacological intervention that can help reduce symptoms of depression is Tai Chi, which involves rhythmic movements and can improve physical and psychological balance. Objectives: The purpose of this study was to examine how Tai Chi exercises affect depression levels among elderly people living in Purbayan Village. Methods: This study used a quantitative approach with a pre-experimental design, in which one group underwent pre-test and post-test assessments. Participants were selected through random sampling based on inclusion criteria, which required elderly individuals who were able to perform daily activities independently. Data were collected using the Indonesian version of the Patient Health Questionnaire-9 (PHQ-9), which showed validity scores ranging from 0.508 to 0.907. The intervention involved Tai Chi exercises consisting of eight movements, performed independently at home for 30 minutes per session, three times a week. Results: The results showed a decrease in the average depression score of 4.9 after the Tai Chi exercise intervention. Statistical analysis using a paired t-test showed a p-value of 0.000 (< 0.05), indicating a significant effect of the intervention. Conclusion: Tai Chi exercises have been proven to reduce depression levels in older adults. This intervention has been proven effective as a non-pharmacological approach to improving mental well-being and overall quality of life among older adults. Keywords: Tai Chi, Depression, Elderly, Mental Health